2015
DOI: 10.1007/s10620-015-3776-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered Bile Acid Metabolome in Patients with Nonalcoholic Steatohepatitis

Abstract: Background & Aims The prevalence of non-alcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH) is increasing at an alarming rate. The role of bile acids in the development and progression of NAFLD to NASH and cirrhosis is poorly understood. This study aimed to quantify the bile acid metabolome in healthy subjects and patients with non-cirrhotic NASH under fasting conditions and after a standardized meal. Methods Liquid chromatography tandem mass spectroscopy was used to quantify 30 serum and 16 uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
229
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(252 citation statements)
references
References 41 publications
15
229
1
7
Order By: Relevance
“…Elevated serum total bile acids in NASH were first reported by Ferslew et al 37. Using approaches that are complementary to ours, Mouzaki et al 17 concluded that bile acid production is elevated in NAFLD livers, based on the findings that faecal total bile acid and faecal primary bile acid levels are elevated in patients with NAFLD, and that serum marker of bile acid synthesis 7-alpha-hydroxy-4-cholesten-3-one is elevated in NAFLD.…”
Section: Discussionmentioning
confidence: 61%
“…Elevated serum total bile acids in NASH were first reported by Ferslew et al 37. Using approaches that are complementary to ours, Mouzaki et al 17 concluded that bile acid production is elevated in NAFLD livers, based on the findings that faecal total bile acid and faecal primary bile acid levels are elevated in patients with NAFLD, and that serum marker of bile acid synthesis 7-alpha-hydroxy-4-cholesten-3-one is elevated in NAFLD.…”
Section: Discussionmentioning
confidence: 61%
“…Human samples were obtained from a single-center, case:control study of male and female patients with biopsy-confirmed NASH (n=7) and corresponding healthy volunteer controls (n=15) (18, 19). The inclusion and exclusion criteria have been described in detail previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of bile acids such as CDCA, DCA and ursodeoxycholic acid are increased in serum and urine samples of patients with NASH compared with healthy subjects 84. Levels of cholic acid are increased in liver tissues from patients with NASH 85.…”
Section: Microbiota-derived Metabolites In Nafldmentioning
confidence: 99%